2008
DOI: 10.1074/jbc.m706610200
|View full text |Cite
|
Sign up to set email alerts
|

Novel Inhibitors for Murine and Human Leukemia Inhibitory Factor Based on Fused Soluble Receptors

Abstract: Proinflammatory cytokines such as tumor necrosis factor (TNF), 2 interleukin-1␤ (IL-1␤), or interleukin-6 (IL-6) have been identified as promising therapeutic targets in the treatment of chronic inflammation. A dimeric soluble TNF receptor is currently used for the treatment of inflammatory diseases caused by elevated TNF expression (1). Whereas TNF signals through a receptor homotrimer, most cytokines signal through receptor complexes consisting of two or more different receptor subunits. In this case, the re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 45 publications
0
22
0
Order By: Relevance
“…By contrast, a similar approach taken to develop a murine LIF fusion protein (i.e. mLIF-RFP) showed that mLIF-RFP or hLIF-RFP blocked STAT3 activation induced by murine or human LIF, respectively, but RFP inhibited neither IL-6 nor OSMinduced STAT3 phosphorylation in the several cell lines that were tested, including COS-7, HEK and mouse embryo fibroblast cells [168]. The results of these studies, when taken together, suggested the distinct possibility that similar fusion protein strategies might be employed for creating potent and specific inhibitory biologics for other pro-inflammatory cytokines such as IL-27/IL-28 [9,169] IL-31 [170], as well OSM [171], that were reported to either activate JAK/STAT or as in the case of IL-32 [1,24,172] induce TNF-, IL-1 and IL-6 gene expression via SAP/MAPK activation [172].…”
Section: Anti-il-6mentioning
confidence: 91%
See 1 more Smart Citation
“…By contrast, a similar approach taken to develop a murine LIF fusion protein (i.e. mLIF-RFP) showed that mLIF-RFP or hLIF-RFP blocked STAT3 activation induced by murine or human LIF, respectively, but RFP inhibited neither IL-6 nor OSMinduced STAT3 phosphorylation in the several cell lines that were tested, including COS-7, HEK and mouse embryo fibroblast cells [168]. The results of these studies, when taken together, suggested the distinct possibility that similar fusion protein strategies might be employed for creating potent and specific inhibitory biologics for other pro-inflammatory cytokines such as IL-27/IL-28 [9,169] IL-31 [170], as well OSM [171], that were reported to either activate JAK/STAT or as in the case of IL-32 [1,24,172] induce TNF-, IL-1 and IL-6 gene expression via SAP/MAPK activation [172].…”
Section: Anti-il-6mentioning
confidence: 91%
“…IL-6RFP) [168]. In structural studies IL-6RFP was shown to be more stable than an IL-6/sIL6R /sgp130 complex.…”
Section: Anti-il-6mentioning
confidence: 97%
“…These mediators can be subdivided in two subgroups: those recruiting three receptor components via sites 1, 2 and 3, and a second subgroup (IL-31, OSM, LIF, IL-27), requiring the involvement of only two receptor subunits recognized through interactions with the sites 2 and 3 (14). A recent report described the possibility of neutralizing the LIF response by using a mouse construction inhibiting interactions between the receptor subunits and sites 2 and 3 of the cytokine (40). Our findings extend this approach to the human IL-31 receptor and emphasize the specificity of the observed neutralizing response.…”
Section: Discussionmentioning
confidence: 99%
“…This strategy was successfully applied to generate inhibitors for the IL-6-type family members IL-6 and leukemia inhibitory factor (LIF) and might be transferred to the IL-23 signaling complex [134][135][136], by fusion of sIL-23R and sIL-12Rβ1.…”
Section: Molecular Strategies To Block Il-23 Receptor Complex Assemblymentioning
confidence: 99%